ENGAGING MINDS, IGNITING POTENTIAL: EXPLORING INTERACTIVE TEACHING METHODS IN PRIMARY EDUCATION (Academia Science Repository, 2023)
This article explores the importance of interactive teaching methods in primary education, emphasizing their role in enhancing student engagement, promoting collaboration, and fostering critical thinking. It discusses the benefits of differentiated instruction, authentic assessment, and student empowerment through hands-on learning, technology integration, collaborative activities, and play-based approaches. The article highlights the value of creating dynamic and immersive learning environments that cater to diverse student needs, fostering a lifelong love for learning and equipping students with essential 21st-century skills.